PENGARUH BUDAYA ORGANISASI, ETOS KERJA, INDEPENDENSI AUDITOR, INTEGRITAS AUDITOR DAN PEMAHAMAN GOOD GOVERNANCE TERHADAP KINERJA AUDITOR - Chandra Wanadri; Christina Dwi Astuti (Jurnal Akuntansi Trisakti, 2015)
This study aims to determine the effect of Organizational Culture, Work Ethics, Auditor Independence, Integrity Auditor and Understanding of Good Governance on Auditor Performance. The sample used in this study consists of 121 auditors, internal auditors and external auditors are included in Jakarta. Samples were randomly distributed using a purposive sampling method. The method used in this study is a multiple linear regression. This Study show that the results of Auditor Independence can affect auditor performance significantly, because of the significant level of the t test was under 0.05. while the other independent variables, such as Cultural Organization, Work Ethics, Integrity Auditor and understanding of Good Governance, together with the auditor independence joinly affect auditor performance, because the level of the F test is significant in under 0.05. For future research, it is advisable to further expand the sample to be used in research, as well as adding variables that need to be researched and also accompany the respondents in the questionnaire in order to obtain a thorough and accurate answer.